Revised criteria of International Workshop on Ocular Sarcoidosis (IWOS) for the diagnosis of ocular sarcoidosis - Mochizuki, Manabu; Smith, Justine R; Takase, Hiroshi; Kaburaki, Toshikatsu; Acharya, Nisha R; Rao, Narsing A (British journal of ophthalmology, 2019)
AimsInternational criteria for the diagnosis of ocular sarcoidosis (OS) was established by the first International Workshop on Ocular Sarcoidosis (IWOS) and validations studies revealed certain limitations of the criteria. To overcome the limitations, revised IWOS criteria was established in an international meeting. This manuscript was aimed at reporting the revised IWOS criteria.MethodsA consensus workshop was carried out to discuss and revise the IWOS criteria. The workshop was held on 27 April 2017, in Nusa Dua, Bali, Indonesia. Prior to the workshop, a questionnaire proposing revised criteria and consisting of one item for differential diagnosis, seven items for ocular clinical signs, 10 items for systemic investigations and three categories of diagnostic criteria was circulated to 30 uveitis specialists. Questionnaire items with over 75% support were taken as consensus agreement; items with below 50% support were taken as consensus disagreement and items with 50%–75% support were discussed at the workshop. Of the latter items, those supported by two-thirds majority in the workshop were taken as consensus agreement.ResultsThe survey and subsequent workshop reached consensus agreements of the revised criteria for the diagnosis of OS as follows: (1) other causes of granulomatous uveitis must be ruled out; (2) seven intraocular clinical signs suggestive of OS; (3) eight results of systemic investigations in suspected OS and (4) three categories of diagnostic criteria depending on biopsy results and combination of intraocular signs and results of systemic investigations.ConclusionsRevised IWOS criteria were proposed by a consensus workshop.